THE MATERIALS UTILISED IN THE EARTHEN BUILDINGS SITED IN THE DRÂA VALLEY (MOROCCO ): MINERALOGICAL AND MECHANICAL CHARACTERISTICS - Baglioni, Eliana; Fratini, Fabio; Rovero, Luisa (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The paper reports the results of an experimental investigation carried out in order to determinate the physical and mechanical properties of the earth material utilized in the Drâa valley (Morocco) for the building made of pisé and adobe. In Drâa valley, a millennial heritage of earthen buildings of great architectonic value (ksar and kasbah) is present. The analyzes were carried out on different kind of earth, utilized both for adobe and pisé building. The earths were characterized through the study of the mineralogical composition, the determination of the grain size and the consistency limits. The mechanical properties were determined both in laboratory through mechanical test and in situ through sclerometers analysis. The results of the compositional, physical and mechanical analyses makes it possible to evaluate the suitability of the utilized earths as construction materials and to propose improvement methods.